Training and Mentoring of Manggarai Women Farmers Group to Make Eco-Enzyme from Agricultural Waste as Organic Fertilizer - Halim Halim; Vit Neru Satrah; Asniah Asniah (International Journal Of Community Service, 2024)
The concept of organic farming based on local wisdom to realize the healthy living community movement program is very important to be implemented by referring to the concept of environmentally friendly and sustainable agriculture. One of the wastes that does not get attention to be managed properly is agricultural waste. Unprocessed agricultural waste will become a source of environmental pollution, a source of disease, and disrupt ecological cleanliness. Therefore, agrarian waste needs to be managed properly so that it can provide benefits to the lives of the community in general and farmers in particular. This community-based empowerment activity aims to assist and train the Manggarai Women Farmers Group in making eco-enzymes from agricultural waste as liquid organic fertilizers. Training and assistance activities are carried out with stages of socialization, training and assistance, application of technology, monitoring, and evaluation. The results of the activity show that there has been a change in the mindset of the members of the Manggarai Women Farmers group to utilize agricultural waste as a material for making eco-enzymes as organic fertilizers in plant cultivation.